Cytokinins in tobacco and wheat chloroplasts. Occurrence and changes due to light/dark treatment - Benková, E; Witters, E; Van Dongen, W; Kolár, J; Motyka, V; Brzobohatý, B; Van Onckelen, H A; Machácková, I (Plant physiology, 1999)
Although cytokinins (CKs) affect a number of processes connected with chloroplasts, it has never been rigorously proven that chloroplasts contain CKs. We isolated intact chloroplasts from tobacco (Nicotiana tabacum L. cv SR1) and wheat (Triticum aestivum L. cv Ritmo) leaves and determined their CKs by liquid chromatography/tandem mass spectroscopy. Chloroplasts from both species contained a whole spectrum of CKs, including free bases (zeatin and isopentenyladenine), ribosides (zeatin riboside, and isopentenyladenosine), ribotides (isopentenyladenosine-5'-monophosphate, zeatin riboside-5'-monophosphate, and dihydrozeatin riboside-5'-monophosphate), and N-glucosides (zeatin-N(9)-glucoside, dihydrozeatin-N(9)-glucoside, zeatin-N(7)-glucoside, and isopentenyladenine-N-glucosides). In chloroplasts there was a moderately higher relative amount of bases, ribosides, and ribotides than in leaves, and a significantly increased level of N(9)-glucosides of zeatin and dihydrozeatin. Tobacco and wheat chloroplasts were prepared from leaves at the end of either a dark or light period. After a dark period, chloroplasts accumulated more CKs than after a light period. The differences were moderate for free bases and ribosides, but highly significant for glucosides. Tobacco chloroplasts from dark-treated leaves contained zeatin riboside-O-glucoside and dihydrozeatin riboside-O-glucoside, as well as a relatively high CK oxidase activity. These data show that chloroplasts contain a whole spectrum of CKs and the enzymatic activity necessary for their metabolism.
Keywords: Nicotiana; Chlorophyll; glukosidy; Cytokinins; Plant Leaves; chloroplasty; Plants, Toxic; světlo; chlorofyl; pšenice; listy rostlin; časové faktory; Light; Darkness; jedovaté rostliny; oxidoreduktasy; tabák; Chloroplasts; Glucosides; Triticum; tma; Oxidoreductases; Time Factors; cytokininy